2007
DOI: 10.1080/03004430600563034
|View full text |Cite
|
Sign up to set email alerts
|

Fathers and young children’s literacy experiences in a family environment

Abstract: Research provides evidence that fathers can promote the development of their children's literacy skills, including reading books to them that are appropriate, engaging their children in discussions about books they read, recording in a notebook the books the children have read and encouraging their children to read more books. This review presents some emerging findings and issues in the research literature that are relevant to the role of fathers in promoting their children's literacy learning. It also summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The findings of the reviewed articles (including reviews and meta-analyses), focusing in particular on the association between father involvement and children's cognitive skills, showed a positive and statistically significant association during early childhood (Flouri and Buchanan, 2004; McBride et al, 2005, 2009; Roopnarine et al, 2006; Saracho, 2007b; Downer et al, 2008; Coley et al, 2011; Fagan and Lee, 2012; McWayne et al, 2013; Duursma, 2014; Jeynes, 2015; Kim and Hill, 2015; Baker, 2017, 2018) beyond mothers' parenting (Roopnarine et al, 2006). More specifically, Fagan and Lee (2012) argued that this relationship was significantly strengthened for children living in single-mother households, whereas Coley et al (2011) found that family characteristics were trifling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the reviewed articles (including reviews and meta-analyses), focusing in particular on the association between father involvement and children's cognitive skills, showed a positive and statistically significant association during early childhood (Flouri and Buchanan, 2004; McBride et al, 2005, 2009; Roopnarine et al, 2006; Saracho, 2007b; Downer et al, 2008; Coley et al, 2011; Fagan and Lee, 2012; McWayne et al, 2013; Duursma, 2014; Jeynes, 2015; Kim and Hill, 2015; Baker, 2017, 2018) beyond mothers' parenting (Roopnarine et al, 2006). More specifically, Fagan and Lee (2012) argued that this relationship was significantly strengthened for children living in single-mother households, whereas Coley et al (2011) found that family characteristics were trifling.…”
Section: Resultsmentioning
confidence: 99%
“…As seen, although many studies highlighted that mothers were engaged in their children's education more frequently than fathers (Duursma, 2014; Kim and Hill, 2015; Baker, 2018), at the same time, there is strong evidence that fathers can play a unique role in children's cognitive skills development (Flouri and Buchanan, 2004; McBride et al, 2005, 2009; Roopnarine et al, 2006; Saracho, 2007b; Downer et al, 2008; Fagan and Lee, 2012; McWayne et al, 2013; Duursma, 2014; Jeynes, 2015; Kim and Hill, 2015; Baker, 2017, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(McBride, Dyer, & Laxman, 2013, p. 823). Educators should rely on the wealth of home-based knowledge and implement this knowledge in school-based practices (Saracho, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There is also some research on fathers' involvement in children's schooling (Bronstein, 1984;Flouri, 2005;Flouri & Buchanan, 2003; for a review see Saracho, 2007). For example, Flouri and Buchanan (2003) examined the predictors of fathers' reading to their children.…”
Section: Differences Between Mothers' and Fathers' Teachingmentioning
confidence: 97%